Protection against Experimental Melioidosis following Immunisation with a Lipopolysaccharide-Protein Conjugate - Andrew E. Scott; Sarah A. Ngugi; Thomas R. Laws; David Corser; Claire L. Lonsdale; Riccardo V. D’Elia; Richard W. Titball; E. Diane Williamson; Timothy P. Atkins; Joann L. Prior (Journal of Immunology Research)
Melioidosis is a severe infectious disease caused by Burkholderia pseudomallei. It is refractory to antibiotic treatment and there is currently no licensed vaccine. In this report we detail the construction and protective efficacy of a polysaccharide-protein conjugate composed of B. pseudomallei lipopolysaccharide and the Hc fragment of tetanus toxin. Immunisation of mice with the lipopolysaccharide-conjugate led to significantly reduced bacterial burdens in the spleen 48 hours after challenge and afforded significant protection against a lethal challenge with B. pseudomallei. The conjugate generated significantly higher levels of antigen-specific IgG1 and IgG2a than in lipopolysaccharide-immunised mice. Immunisation with the conjugate also demonstrated a bias towards Th1 type responses, evidenced by high levels of IgG2a. In contrast, immunisation with unconjugated lipopolysaccharide evoked almost no IgG2a demonstrating a bias towards Th2 type responses. This study demonstrates the effectiveness of this approach in the development of an efficacious and protective vaccine against melioidosis.